The role of adipocytokines and endothelial dysfunction with irritable bowel syndrome associated with obesity - Bilooka, Yu.; Fediv, O.; Stupnytska, H.; Bilookyi, V.; Bilookyi, O.; Rohovyi, Y. (Journal of Education, Health and Sport, 2021)
The article contains the analysis of results concerning investigation of adipocytokines content and endothelial dysfunction in 97 patients with irritable bowel syndrome associated with obesity. The blood serum was examined for the content of adipocytokines (leptin, adiponectin, resistin), stable nitrogen monoxide metabolites (nitrites/nitrates), endothelin-1, intercellular adhesion molecule 1 (ICAM-1), and the number of circulating endothelial cells (CEC). Patients with IBS associated with obesity and prevailing diarrhea are found to develop a prominent imbalance of adipocytokines which is manifested in high levels of leptin and resisin and low level of adiponectin in the blood serum. Endothelial dysfunction evidenced by a high level of endothelin-1, the number of circulating endothelial cells, general NO and intercellular adhesion molecules 1, is characteristic for patients with IBS associated with obesity and prevailing diarrhea.